2003
DOI: 10.1007/s00442-003-1226-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fish introduction on the length of the tail of cryptomonads in mesocosm experiments

Abstract: Two different morphs of the small cryptomonad, Plagioselmis prolonga var. nordica with a posterior tail, were observed during summer and fall in the hypertrophic lake, Lake Kasumigaura, Japan. The tail shortened in mesocosms stocked with planktivorous silver carp ( Hypophthalmichthys molitrix Val.) and elongated by more than 50% in mesocosms from which silver carp were removed. The density of Plagioselmis cells increased significantly upon fish stocking and decreased upon fish removal. The tail length was nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…(1998) observed large variations in C. hirundinella morphology in experiments with no change in water temperature, suggesting that the appearance of the third posterior horn could have other adaptive advantages. Recent studies (Kim et al. 2003, Lürling 2003) suggested that the observed phenotypic variability in different phytoplankton taxa could be related to the presence of zooplankton grazers or planktivorous fish.…”
mentioning
confidence: 99%
“…(1998) observed large variations in C. hirundinella morphology in experiments with no change in water temperature, suggesting that the appearance of the third posterior horn could have other adaptive advantages. Recent studies (Kim et al. 2003, Lürling 2003) suggested that the observed phenotypic variability in different phytoplankton taxa could be related to the presence of zooplankton grazers or planktivorous fish.…”
mentioning
confidence: 99%
“…某些 蓝藻在浮游动物释放的化学信号介导下, 观察到"诱导 防御"现象: 在浮游动物的胁迫下, 几种铜绿微囊藻的 毒素产量显著增加 [74] . 一些藻类群体(如鞭毛藻、角藻 和黑角藻等)作为对鱼类捕食的防御机制, 会表现出形 态变化 [75] . 然而, 关于鱼类捕食压力对蓝藻生理生态影 响的研究较少.…”
Section: 鱼类摄食对蓝藻生理生态的影响unclassified
“…There is evidence that the cryptomonad Plagioselmis prolonga var. nordica produce longer tails in the presence of the silver carp Hypophthalmichthys molitrix (Kim et al 2003). However, these experiments were conducted in mesocosms that also contained zooplankton, and thus the morphological response in P. prolonga may have been a direct effect of changes in zooplankton density and not related to the presence of fish kairomone.…”
mentioning
confidence: 99%